2000
DOI: 10.1007/s002530051632
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of carotenoid accumulation in Escherichia coli by modulation of the isoprenoid precursor pool with expression of deoxyxylulose phosphate synthase

Abstract: The recently discovered non-mevalonate pathway to isoprenoids, which uses glycolytic intermediates, has been modulated by overexpression of Escherichia coli D-1-deoxyxylulose 5-phosphate synthase (DXS) to increase deoxyxylulose 5-phosphate and, consequently, increase the isoprenoid precursor pool in E. coli. Carotenoids are a large class of biologically important compounds synthesized from isoprenoid precursors and of interest for metabolic engineering. However, carotenoids are not ordinarily present in E. col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
2
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(93 citation statements)
references
References 20 publications
1
89
2
1
Order By: Relevance
“…For example, overexpression of DXS or GGPPS in combination with a carotenoid cluster significantly enhanced carotenoids produced in an E. coli bacterial platform (Wang et al, 1999;Matthews and Wurtzel, 2000). Similar examples in other plants have shown that overexpression of genes for certain upstream precursor pathway enzymes (DXS, DXR, or HDR) plus a downstream pathway enzyme forced pathway flux to the downstream pathway (BotellaPavia et al, 2004;Carretero-Paulet et al, 2006;MunozBertomeu et al, 2006).…”
Section: Upstream Isoprenoid Biosynthesis Controls Downstream Endospementioning
confidence: 83%
See 1 more Smart Citation
“…For example, overexpression of DXS or GGPPS in combination with a carotenoid cluster significantly enhanced carotenoids produced in an E. coli bacterial platform (Wang et al, 1999;Matthews and Wurtzel, 2000). Similar examples in other plants have shown that overexpression of genes for certain upstream precursor pathway enzymes (DXS, DXR, or HDR) plus a downstream pathway enzyme forced pathway flux to the downstream pathway (BotellaPavia et al, 2004;Carretero-Paulet et al, 2006;MunozBertomeu et al, 2006).…”
Section: Upstream Isoprenoid Biosynthesis Controls Downstream Endospementioning
confidence: 83%
“…Extensive studies have implicated phytoene synthase (PSY), the first committed enzyme, as rate controlling for endosperm carotenoids (Randolph and Hand, 1940;Palaisa et al, 2003;Gallagher et al, 2004;Wong et al, 2004;Pozniak et al, 2007;Li et al, 2008aLi et al, , 2008b. However, upstream precursor pathways may also positively influence carotenoid accumulation (Matthews and Wurtzel, 2000;Mahmoud and Croteau, 2001), while downstream degradative pathways may deplete the carotenoid pool (Galpaz et al, 2008). We decided to utilize natural genetic and biochemical variation in a maize germplasm collection to identify potential transcriptional control points affecting endosperm carotenoid accumulation, since transcriptional control plays a large role in carotenogenesis (Giuliano et al, 2008).…”
mentioning
confidence: 99%
“…Other factors that might additionally affect flux in roots may be attributed to the upstream nonmevalonate isopentenyl diphosphate biosynthetic pathway for which expression of certain enzymes has been shown to impact flux to carotenoids in maize (R. Vallabhaneni and E.T. Wurtzel, unpublished data) and in other organisms (Matthews and Wurtzel, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Jasmonate elicitation increased the expression level of a number of biosynthesis genes including DXS (van der Fits and Memelink 2000), encoding an enzyme of upstream part of the MEP pathway. Overexpressing the DXS gene in transgenic Escherichia coli resulted in an increased accumulation of the carotenoids lycopene (Matthews and Wurtzel 2000), b-carotene (Albrecht et al 1999) or zeaxanthin (Albrecht et al 1999;Matthews and Wurtzel 2000). Furthermore, the GGPPS transcript levels in Taxus canadensis cell suspension cultures (Hefner et al 1998) and Corylus avellana leaves (Wang et al 2010) were up-regulated after MeJA treatment, even though no significant change in GGPPS expression was observed in C. roseus cell suspension cultures (Thabet et al 2012).…”
Section: Analysis Of Carotenoidsmentioning
confidence: 99%